CCL19, a B Cell Chemokine, Is Related to the Decrease of Blood Memory B Cells and Predicts the Clinical Response to Rituximab in Patients With Rheumatoid Arthritis. Issue 9 (26th August 2013) - Sellam, Jérémie; Rouanet, Stéphanie; Hendel‐Chavez, Houria; Miceli‐Richard, Corinne; Combe, Bernard; Sibilia, Jean; Le Loët, Xavier; Tebib, Jacques; Jourdan, Rosemary; Dougados, Maxime; Taoufik, Yassine; Mariette, Xavier
Abstract : Objective: Migration of B cells from peripheral blood to the synovium in patients with rheumatoid arthritis (RA) may predict clinical response to rituximab (RTX). We undertook this study to investigate whether serum levels of chemokines involved in B cell trafficking are correlated with blood levels of memory B cells or serum levels of B cell activation biomarkers before B cell depletion and whether chemokine levels predict RTX responsiveness. Methods: Blood B cell subsets were analyzed by flow cytometry (CD27, IgD), and serum B cell activation biomarkers (rheumatoid factor, anti–cyclic citrullinated peptide, free light chains, IgG, IgA, IgM, and BAFF) were measured in 208 RA patients and 70 control subjects. Serum CCL19, CXCL12, and CXCL13 chemokine levels in patients and controls were determined by enzyme‐linked immunosorbent assay. The first course of RTX was administered to RA patients, and the response was evaluated at week 24 according to European League Against Rheumatism (EULAR) criteria. Results were expressed as the odds ratio (OR) and 95% confidence interval (95% CI). Results: Levels of all chemokines were increased in RA patients compared with controls, and levels were inversely correlated with CD27+ memory B cell frequency. CCL19 and CXCL13 levels correlated with levels of 6 serum B cell biomarkers and 4 serum B cell biomarkers, respectively. By univariate analysis, the CCL19 level was positively associated with EULAR response (OR 1.43 [95% CI 1.08–1.90], P = 0.01). By multivariate analysis, the CCL19 level was predictive of a response to RTX (OR 1.48 [95% CI 1.06–2.06], P = 0.02), but this did not persist after adjustment for autoantibody status. Conclusion: CXCL13 and CCL19 reflect blood B cell disturbances and their levels correlate with those of other serum B cell biomarkers. CXCL13 and CCL19 are, therefore, surrogate measures for serum B cell biomarkers in RA. Serum CCL19 measurement is a new hallmark of the B cell–mediated RA subtype and may predict clinical response to RTX.